Cross-processing herring and salmon co-products with agricultural and marine side-streams or seaweeds produces protein isolates more stable towards lipid oxidation. (15th July 2022) - Zhang, Jingnan; Abdollahi, Mehdi; Alminger, Marie; Undeland, Ingrid
Highlights: Fish co-products were pH-shift processed with antioxidant-containing raw materials. This cross-processing reduced lipid oxidation during protein isolation/storage. Lingonberry press-cake greatly limited MDA/HHE formation during isolation/storage. Apple pomace and Ulva lowered the max level of MDA/HHE in herring protein isolates. Pigments from helpers changed the color of protein isolates. Abstract: Herring and salmon filleting co-products were pH-shift processed together with seven antioxidant-containing raw materials ("helpers") including lingonberry-, apple-, oat-, barley- and shrimp-co-products, and two seaweeds ( Saccharina latissima, Ulva fenestrata ) to produce protein isolates stable towards lipid oxidation. Malondialdehyde (MDA) and 4-hydroxy-(E)-2-hexenal (HHE) levels revealed that all helpers, except shrimp shells, to different extents retarded lipid oxidation both during pH-shift-processing and ice storage. The three helpers performing best were: lingonberry press-cake > apple pomace ∼ Ulva . Color of protein isolates was affected by helper-derived pigments (e.g., anthocyanins, carotenoids, chlorophyll) and lipid oxidation-induced changes (e.g., metHb-formation, pigment-bleaching). In conclusion, combining fish co-products with other food side-streams or seaweeds during pH-shift processing appears a promising new tool to minimize lipid oxidation of protein isolates, both during their production and subsequent storage. Lingonberry press-cake was the most efficient helper but provided dark color which may narrow product development possibilities, something which requires further attention.